A Feedback Model for Applied Research on Tobacco Control - Gail G. Sneden, MA; Amy S. Gottlieb-Nudd, MPH; Nell H. Gottlieb, PhD; Philip P. Huang, MD, MPH (Centers for Disease Control and Prevention, 2006)
Although the health communication program feedback cycle is frequently referenced, the steps for moving between or within the sections of the model in a public health environment are rarely described. We detail the process by which the Texas Tobacco Research Consortium implemented the stage of "assessing effectiveness and making refinement" and expanded it to include a program assessment feedback model. Tools were developed to move the consortium through five stages of the expanded program assessment feedback model: 1) formulate research questions using logic models to identify key evaluation items, 2) format data displays from multiple data sources to address research questions, 3) use a facilitated group process to present and review research findings, 4) prepare group recommendations, and 5) involve local partners to translate recommendations into practice. The process allowed us to sift through a large volume of information and prepare data-based program recommendations. A Web-based reporting system provided timely access to community-based program activity data and process indicators that, when linked to logic models, provided actionable items for program improvement. Partnerships among researchers and state and local practitioners created the conditions for implementing the recommendations. Program changes included revisions to program materials, target audiences, and evaluation instruments for a community-based tobacco-cessation campaign. The systematic approach allowed translation of research into practice and should be applicable to other areas of population-based health promotion.